Good Beginnings: Decolonizing Protocols and Agreements or Mouse Crosses River - Geller, Philip (Percées)

(untitled) (Société québécoise d'études théâtrales (SQET), 2023)
Mouse tries to cross River. Philip attempts to create theatre in an institutional context. What could go wrong? What could go right? A decolonizing offering in how we enter artistic and collaborative relations. What protocols, practices, and understanding are required to have a good beginning?